(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study examines the complex issues faced by rural consumers in the Kumbakonam area of Tamil Nadu through an empirical investigation. By gathering primary data from rural households using a structured questionnaire, the research examines the economic, informational, infrastructural, digital, and market-related barriers that influence consumer behavior. Descriptive and inferential statistical methods, such as mean, standard deviation, ANOVA, Multivariate analysis, and Structural Equation Modeling (SEM), are utilized to examine the relationships among key constructs. The findings reveal that information asymmetry, price sensitivity, restricted market access, and digital exclusion have a significant impact on the purchasing choices of rural consumers. This study provides region-specific insights into the rural marketing literature and offers practical recommendations for policymakers, marketers, and educational institutions to enhance rural consumer empowerment.